PROFESSIONAL COMPETENCE AS A PEDAGOGICAL PROBLEM (Pedagogy of Higher and Secondary Education, 2022)
The article is devoted the problem of modernization of higher education of Ukraine on kompeteninisniy basis. In the article scientific literature is analysed on this question. The author of the article exposed component consepts "professional jurisdiction", defined the features of concepts "competence".
Keywords: professional jurisdiction; key jurisdictions; competence